The role of marshall bundle epicardial connections in atrial tachycardias after atrial fibrillation ablation. (24th May 2021) - Vlachos, K; Denis, A; Kitamura, T; Takigawa, M; Frontera, A; Martin, R; Bourier, F; Martin, CA; Cheniti, G; Pambrun, T; Sacher, F; Hocini, M; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Atrial tachycardias (ATs) are often seen in the context of AF ablation. Objectives: We evaluated the role of the Marshall bundle (MB) network in left atrial (LA) ATs using high-density high-spatial resolution 3D mapping. Methods: 199 post-AF ablation LA tachycardias were mapped in 140 consecutive patients (112 (80%) males, mean age: 61.8 years); 133 (66.8%) were macro-reentrant and 66 (33.2%) were scar-related re-entry. MB-dependent perimitral AT (PMAT) was diagnosed where the difference between the post pacing interval and the tachycardia cycle length (PPI-TCL) was <20ms in parts of the expected MB-dependent perimitral circuit (within the VOM, the ridge between the left pulmonary veins and LA appendage (LAA), the anterior LA and between 6- and 11-o'clock of the mitral annulus) and the PPI-TCL was >20ms in areas bypassed by the VOM (the distal coronary sinus (CS), the posterior LA and the mitral isthmus). MB-related re-entry was diagnosed by PPI-TCL <20ms at the left lateral ridge, posterior base of LAA, inferolateral LA or VOM ostium; and PPI-TCL >20ms in the septal annulus. Typically, in MB-dependent localized re-entry, the earliest activation was found along the MB-LA endocardial connection or MB-CS epicardial connection.  Results: The MB network was found to participate in 60 (30.2%) re-entrant ATs, 31 PMATs and 29 localized re-entries. High-frequency multiphasic fragmented electrograms with long duration were often recorded endocardially or epicardially at the MB-LA or MB-CS connections. The amplitude and duration of these signals were 0.5 ± 0.79 mV and 65 ± 40 ms for MB-PMATs and 0.26 ± 0.28mV and 122 ± 67 ms for MB-localized re-entries. Unipolar EGMs at the site of endocardial-epicardial breakthrough had a rS pattern in all MB-related ATs. Of 60 MB-related ATs, 49 (81.6%) terminated with RF ablation, 44 (73.3%) at the MB-LA junction and 5 (8.3%) at the MB-CS junction, while 9 (15%) terminated after 2.5-5 cc of alcohol infusion inside the vein of Marshall (VOM). Of the 31 MB-related macroreentrant ATs, 17 (54.8%) terminated at the MB-LA junction, 5 (16.1%) at the MB-CS junction and 7 (22.6%) with alcohol infusion inside the VOM. Two macroreentries (6.5%) using the MB did not terminate with RF energy either endocardially at the MB-LA junction or epicardially at the MB-CS junction, and we were unable to identify or cannulate the VOM for ethanol infusion. Of the 29 localized re-entrant ATs using the MB, 27 (93.1%) terminated at the MB-LA junction, none terminated at the MB-CS junction and 2 (6.9%) terminated after alcohol infusion. After a mean follow up of 12 months, only 4 patients (6.7%) had AT recurrence. Conclusions: MB re-entrant ATs accounted for up to 29% of the left ATs after AF ablation. Ablation of the MB-LA or CS-MB connections or alcohol infusion inside the VOM is required to treat these arrhythmias.